Development of Motion Graphics Video Based on CPA Approach to Enhance Elementary Students' Mathematical Creative Thinking Ability - Eka Putri, Hafiziani; Nuraeni, Fitri; Herlina Arrum, Aisyah; Karisma Pertiwi, Cahya; Nurhanifa, Rifa; Wulandari, Hayani (KnE Social Sciences, 2024)
It is important to develop the creative thinking ability of elementary school students so they can tackle the challenges of today’s world. This skill can be enhanced through learning activities at school, particularly in subjects like mathematics. This study aimed to create motion graphics video teaching materials based on the CPA approach to help improve students’ creative thinking abilities. The 4-D model was used to develop these materials, which involves defining, designing, developing, and disseminating the materials. The experts used teaching materials assessment sheets and test items to evaluate the effectiveness of the materials. The results showed that mathematics teaching materials using motion graphics video teaching based on the CPA approach were successful in improving students’ creative thinking skills. These teaching materials can be used in elementary mathematics education and for further research purposes. Keywords: CPA approach, mathematical creative thinking ability, motion graphics video.